The Relationship of Anxiety Levels with Frequency of Dispneu Exacerbation in Asthma Bronchial's Patients at SMF Pulmo, Soebandi General Hospital, Jember - Michael Hostiadi; Alif Mardijana; Edi Nurtjahja (Journal of Agromedicine and Medical Sciences, 2015)
Asthma is a chronic inflamation of respiratory tract which cause bronchial hypereactivity to some triggers with dispneu as the main symptomp. Stress and emotional disturbance like anxiety can be the trigger of asthma attack. This research is to find out the relationship between anxiety level and the frequency of dispneu in asthma bronchial patients at SMF Pulmo, dr. Soebandi General Hospital, Jember. This research used a cross sectional observational analytical method and HARS questionare. Based on our observation to 30 patients, Chi square analytical test showed 0,000 significancy level with p < 0,05. It means that there is a relationship of anxiety levels with the frequency of dispneu in asthma bronchial patients at SMF Pulmo, dr.Soebandi General Hospital, Jember.   Keywords: anxiety, dispneu, asthma bronchial